Attributional Analysis Of Immoral Behavior - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1986)
ABSTRACT Eighty eight college students, half male and half female, were requested to rate stories depicting an actor engaging in immoral behaviors in terms of the actor's responsibility for the behavior and the negativity of behavior. Three variables were manipulated in the stories : sex of the actor, sex-type of behavior, and the motive for the behavior. The results showed that when the motive of behavior was for gain, subjects evaluated the behavior more negatively than when the motive was for avoiding loss. The motive of behavior was also found to interact with the sex-type of behavior. Male-typed behaviors were evaluated more negatively under the gain motive, while female-typed behaviors were evaluated equally negative in both motive conditions. Subjects with high achievement motivation perceived the immoral behavior more negatively as compared to the low achievement motivation subjects. Female actors tended to be rated more negatively than male actors. Keywords: Immoral Behavior